2006
DOI: 10.1097/01.ta.0000204150.78156.a9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-slice CT Angiography for Arterial Evaluation in the Injured Lower Extremity

Abstract: MCTA is a sensitive and specific non-invasive imaging modality for arterial evaluation in the injured lower extremity that may replace catheter-based angiography in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(71 citation statements)
references
References 31 publications
1
69
0
1
Order By: Relevance
“…With a sensitivity of 99%-100% and specificity of 87%-100%, CT angiography (CTA) has replaced conventional angiography in most cases. [15][16][17] While duplex ultrasound is a diagnostic alternative with similar sensitivity and specificity, studies have often found diagnostic accuracy to be user dependent. 14,18 Timing of presentation after injury plays a critical role in a patients' outcome.…”
Section: Discussionmentioning
confidence: 99%
“…With a sensitivity of 99%-100% and specificity of 87%-100%, CT angiography (CTA) has replaced conventional angiography in most cases. [15][16][17] While duplex ultrasound is a diagnostic alternative with similar sensitivity and specificity, studies have often found diagnostic accuracy to be user dependent. 14,18 Timing of presentation after injury plays a critical role in a patients' outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Other options such as duplex ultrasonography (100% sensitivity and 97% specificity for clinically significant arterial injury) or CT angiography (95-100% sensitivity and 97-98% specificity) have also been described. [21][22][23] Even though, serial neurovascular examinations have shown equal sensitivity and specificity compared to obtaining a formal angiographic study, we have adopted a policy that ensures angiographic examination of all knee dislocations. Despite these efforts our amputation rate remains at 25% (seven of 28 patients) of diagnosed vascular injuries.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Additionally, an increasing number of emergency physicians prefer MDCT over catheter-based angiography.…”
Section: Discussionmentioning
confidence: 99%